Introducing the NGSS in Preservice Teacher Education - Hill, Tiffany; Davis, Jeni; Presley, Morgan; Hanuscin, Deborah (Innovations in Science Teacher Education, 2019)
While research has offered recommendations for supporting inservice teachers in learning to implement the NGSS, the literature provides fewer insights into supporting preservice teachers in this endeavor. In this article, we address this gap by sharing our collective wisdom generated through designing and implementing learning experiences in our methods courses. Through personal vignettes and sharing of instructional plans with the science teacher education community, we hope to contribute to the professional knowledge base and better understand what is both critical and possible for preservice teachers to learn about the NGSS.